(-)-Kusunokinin as a Potential Aldose Reductase Inhibitor: Equivalency Observed via AKR1B1 Dynamics Simulation - Tanotnon Tanawattanasuntorn (2022)
(-)-Kusunokinin performed its anticancer potency through CFS1R and AKT pathways. Its ambiguous binding target has, however, hindered the next development phase. Our study thus applied molecular docking and molecular dynamics simulation to predict the protein target from the pathways. Among various candidates, aldo-keto reductase family 1 member B1 (AKR1B1) was finally identified as a (-)-kusunokinin receptor. The predicted binding affinity of (-)-kusunokinin was better than the selected aldose reductase inhibitors (ARIs) and substrates. The compound also had no significant effect on AKR1B1 conformation. An intriguing AKR1B1 efficacy, with respect to the known inhibitors (epalrestat, zenarestat, and minalrestat) and substrates (UVI2008 and prostaglandin H2), as well as a similar interactive insight of the enzyme pocket, pinpointed an ARI equivalence of (-)-kusunokinin. An aromatic ring and a γ-butyrolactone ring shared a role with structural counterparts in known inhibitors. The modeling explained that the aromatic constituent contributed to π-πattraction with Trp111. In addition, the γ-butyrolactone ring bound the catalytic His110 using hydrogen bonds, which could lead to enzymatic inhibition as a consequence of substrate competitiveness. Our computer-based findings suggested that the potential of (-)-kusunokinin could be furthered by in vitro and/or in vivo experiments to consolidate (-)-kusunokinin as a new AKR1B1 antagonist in the future.